Pengaruh Budaya Organisasi Dan Gaya Kepemimpinan Terhadap Kinerja Pegawai Pada Dinas Pendidikan, Pemuda Dan Olahraga Kabupaten Trenggalek - Wawan Catur Prasetyo; Sonny Subroto Maheri Laksono (Universitas Islam Kadiri, 2023)
The aim of this research is to determine and analyze the influence of organisasonal culture and leadership style on employee performance at Dinas Pendidikan Pemuda dan Olahraga Kabupaten Trenggalek. The research includes quantitative researce because the approach use research submission, process, hyopothesis, analysis, data analysis, data conclution and writing using aspectsof measurement, calculation, formulas and certaintyof numerical data. The researchsubject is employee Dinas Pendidikan Pemuda dan Olahraga Kabupaten Trenggalek. Data analysis using multiple linear regression formulas and hypothesis testing. The research result showed that it was achievedsimultanesly nilaiF hitung 36,181 bigger in comparatin nilaiF tabe l3.11and Nilai H0. This indicates that the research result reject Ho. This it can be concluded that organization culture and leadership style are positive and significant on employee performance.